Successful induction of remission with azacitidine, venetoclax, and dasatinib followed by allogeneic hematopoietic stem cell transplantation in a patient with Philadelphia chromosome-positive mixed phenotype acute leukemia (B/myeloid): a case report - Juan Zhang; Yan Huang; Liangkui Luo; Kaikai Huang; Yanbin Pang (Frontiers in Medicine, 2026)
Background Philadelphia chromosome-positive mixed phenotype acute leukemia (Ph + MPAL) is a rare and aggressive hematologic malignancy. The incorporation of tyrosine kinase inhibitors (TKIs) into acute lymphoblastic leukemia (ALL)-like regimens has improved survival for Ph + MPAL. However, the benefit of ALL-like chemotherapy backbones for adult patients, particularly those with bilineal disease, appears limited and is often hampered by significant toxicity. To the best of our knowledge, this case adds to the limited clinical experience regarding the use of azacitidine, venetoclax, and dasatinib in Ph + MPAL. Novel, safer strategies are urgently needed. Case presentation A 32-year-old man presented with a one-week history of fever. Bone marrow examination revealed 83% blasts with two distinct populations: lymphoblasts and monoblasts, confirming bilineal B/myeloid MPAL. Karyotyping showed 45, XY,−7, t(9;22)(q34;q11.2), and the BCR::ABL (p190) fusion gene was positive. Molecular genetics identified an EVI1 fusion gene and an ASXL1 mutation. The patient received one cycle of induction therapy with azacitidine, venetoclax, and dasatinib, augmented with Vincristine, prednisone, and homoharringtonine. Complete remission was achieved following this cycle, with the primary adverse event being grade IV myelosuppression, managed without severe infection, tumor lysis syndrome or organ dysfunction. After three consolidation cycles, flow cytometry showed negative minimal residual disease (MRD); however, BCR::ABL1 remained detectable at 0.3289%. The patient subsequently underwent haploidentical hematopoietic stem cell transplantation (haplo-HSCT). At the most recent follow-up, BCR::ABL1 was undetectable. Conclusion An induction regimen based on azacitidine, venetoclax, and dasatinib may represent a safe and effective therapeutic strategy for adult patients with Ph + , bilineal MPAL, particularly when augmented with agents targeting distinct lineage components.